James Turrell : a retrospective - Govan, Michael; Kim, Christine Y.; Greene, Alison de Lima; Krupp, E. C.; Holzherr, Florian (New York : DelMonico BooksD.A.P., 2023)
"The only comprehensive book on James Turrell is back in print. This definitive monograph presents James Turrell's diverse and extraordinary work--from his Mendota studio days to his monumental Roden Crater. Turrell began using light as a sculptural medium in 1966, and through his sculptures and architectural interventions he is continually asking us to "go inside and greet the light"--evoking the meditative practices of his Quaker upbringing. A critical figure emerging from Los Angeles's exploding art scene of the 1960s, Turrell draws from aviation, psychology, and astronomy in his art. Through ten chapters that survey his various bodies of work, enhanced by thoughtful essays and an insightful interview with the artist, this monograph explores every aspect of Turrell's oeuvre-from his early geometric projections, prints, and drawings, through his installations exploring sensory deprivation and seemingly unmodulated fields of colored light, to two-dimensional experiments with holograms. It also features an in-depth look at Roden Crater--through models, plans, photographs and drawings--that reveals the power and beauty of his magnum opus and its surrounding landscape near Flagstaff, Arizona. Featuring stunning, specially commissioned photography by Florian Holzherr, this is the authoritative book on the pioneering artist and his landmark work" (Provided by publisher.)
boek